Pendampingan Penggunaan Dompet Digital Sebagai Solusi Efisiensi Transaksi Umkm Pedagang Warung/Kios/Toko Di Kota Mataram - Nurabiah Nurabiah; Nur Fitriyah; Herlina Pusparini; Bambang Bambang; Yusli Mariadi; Akram Akram; Yudiawan Saputra; Yusnita Divandra; Mayu Finnari (Universitas Mataram, 2026)
Digital transaction adoption is increasingly essential for micro, small, and medium enterprises (MSMEs), particularly small shops and kiosks in Mataram City, which still face limitations in digital financial literacy. This community service program aims to enhance MSME owners’ understanding and practical skills in using QRIS as an efficient, secure, and transparent digital payment system. The implementation methods include partner needs assessment, pre-test, training and hands-on QRIS practice, post-test evaluation, and continuous assistance through both offline and online consultations. The program involved 10 MSME participants and employed a Likert-scale questionnaire based on three main indicators: basic QRIS knowledge, transaction usage, and payment security and transparency. The results indicate a significant improvement, with the average score increasing from 2.57 (pre-test) to 3.58 (post-test). The distribution of competency levels also shifted toward higher categories after the intervention. These findings demonstrate that structured mentoring effectively improves digital payment literacy and adoption among MSMEs. The program contributes to strengthening financial management, reducing cash transaction risks, and improving business competitiveness in the digital economy era.